Comparative advantage of the EU in global value chains: How important and efficient are new EU members in transition? - Gurgul, Henryk; Lach, Łukasz (Managerial Economics, 2016)
We suggest original modifications and extensions of the recently presented methodological developments in ex-post accounting framework in global value chains in order to obtain empirical results both for the analyzed group of ten CEE economies as well as at acountry-and-sector-specific level. The empirical results confirm that the role of the selected CEE economies in transition in creating value added with respect to the total value added in the European Union in the GVC framework was biggest in the cases of agriculture-, wood-products-, metal-production, and travel-and-tourism-related sectors. We also found that, after two decades of transition, the measures of productivity in the examined economies in 2009 were still much lower as comparedto the EU average for most of the sectors. Moreover, in the transition period, these indexes were increasing, especially after EU accession. In contrary, after two decades of transition, the measures of capital efficiency in the ten CEE economies in 2009 were comparable to the EU average for most of the sectors. Moreover, during this period, the growth rates of these indexes were, in general, positive. However, their growth rates dropped after EU accession.